The Existence of Education as a Rehabilitation, Preventive, Curative, and Moral Development Strategy in Madrasah - N Nuha; Nawwal Tattaqillah; Maher Zain Lillah; S Subhan; Bello Ali; Muhammad Maga Sule; M Mahmudulhassan (Solo Universal Journal of Islamic Education and Multiculturalism, 2024)
The purpose of this study is to analyze the existence of Islamic education as a means of rehabilitation, preventive, curative, and moral formation strategies among students in Madrasas. The type of research used is a case study with a descriptive qualitative approach. Data collection techniques are carried out by using, observation, interviews, and document analysis. Data analysis techniques are carried out by collecting data, reducing data, displaying data, and drawing conclusions, the object of research is carried out at MTS Ma'arif Boyolali. The results of this study show that: (1) There are three types of student problems related to delinquency in Madrasah Tsanawiyyah Ma'arif Boyolali, namely mild delinquency that does not reach violations of the law, moderate delinquency that has the potential to violate the law, severe delinquency that is classified as a violation of the law; (2) The factors causing student delinquency in Madrasah Tsanawiyyah Ma'arif Boyolali are the family environment (broken home), and the school environment (promiscuity); (3). The teacher's strategy to overcome student delinquency in Madrasah Tsanawiyyah Ma'arif Boyolali uses preventive, curative, and rehabilitation strategies (healing) in collaboration with counselling guidance teachers to create participant morale following applicable student norms and behave better.